2016
DOI: 10.1371/journal.pone.0155327
|View full text |Cite
|
Sign up to set email alerts
|

GapBlaster—A Graphical Gap Filler for Prokaryote Genomes

Abstract: The advent of NGS (Next Generation Sequencing) technologies has resulted in an exponential increase in the number of complete genomes available in biological databases. This advance has allowed the development of several computational tools enabling analyses of large amounts of data in each of the various steps, from processing and quality filtering to gap filling and manual curation. The tools developed for gap closure are very useful as they result in more complete genomes, which will influence downstream an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 20 publications
0
22
0
Order By: Relevance
“…In this work, we chose PBJelly and FGAP software in the gap closure analysis and applied to the Chr19 Mercedes+SLR-superscaffolder assembly with ONT dataset to compare gap filling performance. Other subsequent tools did not display obvious improvements in efficiency and accuracy of gap filling [27]. The evaluation of outputs showed that the gap-closing efficiency of TGS-GapCloser was considerably higher than that of other tools, leaving only 322 gaps compared to 1,730 for PBJelly default, 1,016 gaps for FGAP default and 782 for FGAP with overlap option on ( Table 2), thus enhancing the contig NG50 and NGA50 from 11.4kb to 165.2kb and 9.3kb to 117.6kb, respectively, 3.4-6.1-fold than PBJelly and FGAP.…”
Section: Comparison With Other Toolsmentioning
confidence: 94%
See 2 more Smart Citations
“…In this work, we chose PBJelly and FGAP software in the gap closure analysis and applied to the Chr19 Mercedes+SLR-superscaffolder assembly with ONT dataset to compare gap filling performance. Other subsequent tools did not display obvious improvements in efficiency and accuracy of gap filling [27]. The evaluation of outputs showed that the gap-closing efficiency of TGS-GapCloser was considerably higher than that of other tools, leaving only 322 gaps compared to 1,730 for PBJelly default, 1,016 gaps for FGAP default and 782 for FGAP with overlap option on ( Table 2), thus enhancing the contig NG50 and NGA50 from 11.4kb to 165.2kb and 9.3kb to 117.6kb, respectively, 3.4-6.1-fold than PBJelly and FGAP.…”
Section: Comparison With Other Toolsmentioning
confidence: 94%
“…The number of gaps could also be efficiently reduced by FGAP [22], which aligned long reads to the gaps using BLAST algorithm [23]. More tools modified the algorithm and extended for different purposes [24][25][26][27][28]. However, most tools mentioned above share the same crucial shortcoming: they only accept pre-error-corrected long reads or alternative assembled contigs.…”
Section: Problems In Current Tgs Assemblies and Tgs Gap-closing Toolsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been a few tools available for gap filling of genome assembly like GapBlaster [8], FGAP [9], G4ALL [10], GapFiller [11] and GapCloser [12]. They use two approaches to fill gaps: paired end reads and assembled contigs from different software.…”
Section: Introductionmentioning
confidence: 99%
“…They use two approaches to fill gaps: paired end reads and assembled contigs from different software. GapBlaster aligns contigs obtained in the assembly of the genome to a draft of the genome, using BLAST or Mummer, and all identified alignments of contigs that extend through the gaps in the draft sequence are presented to the user for further evaluation via the GapBlaster graphical interface [8]. FGAP also aligns multiple contigs against a draft genome assembly to find sequences that overlap gaps [9].…”
Section: Introductionmentioning
confidence: 99%